Uporaba tehnologije pri obravnavi kronične nerakave bolečine otrok in mladostnikov - Horvat Rauter, Barbara (Rehabilitacija (Ljubljana), 2022)
Chronic non-malignant pain causes suffering and lasting consequences in the functioning and quality of life of 3-5 % of children, adolescents and their families. Interdisciplinary rehabilitation treatment is already established in some other countries, and we are in the process of establishing it at our institute. It includes education, gaining insights into pain symptoms and their occurrence, understanding of pain and the process of changes in therapy. Technology can help us with this already during the treatment, as well as in the transfer and consolidation of the acquired skills. In this paper, we describe the most established forms of technological support: virtual reality, applications to support the change of pain behaviour and technological support in learning relaxation and awareness. We also present the possibilities of using technology to support the family and wider environment.
Keywords: Adolescent; Child; chronic pain; kronična bolečina; otrok; Pain; rehabilitation; Robotics; technology; tehnologija